Results of Source Apportionment by Receptor Modeling of Ulaanbaatar City - S, Lodoysamba; D, Shagjjamba; A, Hasenkopf; G, Gerelmaa; B, Bulgansaikhan (Scientific transaction of the National University of Mongolia. Physics, 2022)
Results of an air pollution source apportionment study using the Positive Matrix Factorization method (PMF) based on sampling of air pollution from a site of Nuclear Research Center, National University of Mongolia 2004-2009 and Zuun ail site 2008-2009 presented. From the statistical analysis of the data, it was possible to allocate factors to sources associated with coal combustion, motor vehicles, road dust, and soil.